2007
DOI: 10.1002/chem.200600803
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Size on Phase Morphology and Li‐Ion Mobility in Nanosized Lithiated Anatase TiO2

Abstract: Sustainable energy storage in the form of Li-ion batteries requires new and advanced materials in particular with a higher power density. Nanostructuring appears to be a promising strategy, in which the higher power density in nanosized materials is related to the dramatically shortened Li-ion diffusion paths. However, nanosizing materials also changes intrinsic material properties, which influence both ionic and electronic conductivity. In this work neutron diffraction is used to show that in addition to thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 35 publications
5
103
0
Order By: Relevance
“…10,11 In nanoscale samples it has been reported that this phase separation is suppressed with the two phases coexisting within a single domain. Stoichiometries that are normally unstable in the bulk become accessible, suggesting a synthetic route to achieving increased charge densities, 12,13 and the electrochemical behavior of lithium insertion into nanotubular anatase has been studied by a number of groups. [14][15][16][17] The historical interest in anatase TiO 2 means that lithium intercalation is relatively well characterized experimentally for the bulk system, providing useful reference data for theoretical studies, and making it a prototypical system when considering the properties of more exotic polymorphs and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In nanoscale samples it has been reported that this phase separation is suppressed with the two phases coexisting within a single domain. Stoichiometries that are normally unstable in the bulk become accessible, suggesting a synthetic route to achieving increased charge densities, 12,13 and the electrochemical behavior of lithium insertion into nanotubular anatase has been studied by a number of groups. [14][15][16][17] The historical interest in anatase TiO 2 means that lithium intercalation is relatively well characterized experimentally for the bulk system, providing useful reference data for theoretical studies, and making it a prototypical system when considering the properties of more exotic polymorphs and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile lithium-ion species in the electrolyte result in a relatively narrow central resonance with a linewidth of approximately 500 Hz, whereas lithium in the electrode material gives rise to a broad signal with a much lower peak height and a linewidth of approximately 5 kHz consistent with earlier findings. [22] It should be realized that at this composition, Li 0.5 TiO 2 is fully converted into the lithium titanate structure and hence has a single crystalline phase. The T 1 relaxation time for lithium in the solid Li 0.5 TiO 2 was determined to be 3-5 s and for lithium in the electrolyte to range from 0.3-1 s depending on the composition of the electrolyte and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recent NMR spectroscopy study [35] of nanosized lithiated anatase revealed further important details of the phase behavior and morphology. The coexistence of the Li-poor and the Li-rich phases is possible only in the particles of the size exceeding 120 nm due to the surface strain (occurring between the phases) which becomes energetically unfavourable in small particles.…”
Section: Special Features Of the Lithium Intercalated Anatase: Phase mentioning
confidence: 99%